Optimization of Website Based Facility Service System at Politeknik Penerbangan Surabaya - Lady Silk Moonlight; Teguh Arifianto; Ahmad Bahrawi; Dewi Ratna Sari; Didi Hariyanto; Putri Dya Citra Nur Kumala Sari (International Journal of Artificial Intelligence Research, 2025)
Technological developments, particularly in the Industry 4.0 era, accompanied by increasing technological literacy among the public, have influenced business operations, making them easier to develop and more widely known. Digital transformation innovations in facility services at the Politeknik Penerbangan Surabaya were carried out to improve administrative efficiency, information, and service speed. This study aims to develop a web-based facility service information system with the Laravel framework and online payments using the Midtrans payment gateway that can be accessed by internal and external users of the institution more easily and transparently. The development of this system uses the Waterfall Software Development Life Cycle (SDLC) method. The results of the study show that this system is able to manage facility data, transactions, availability, and transaction history in an integrated and real-time manner. The integration of Midtrans into the system not only makes transactions fast and secure, but also provides convenience and security protection for customers. The implementation of this system has been proven to increase efficiency, speed up the service process, minimize recording errors, while expanding service access for users from outside the institution easily and effectively. In addition, with the institution's digital development system, strategic decision-making has also become easier